SCREENING OF MARINE BROWN ALGAE ASSOCIATED POTENTIAL BACTERIA PRODUCING ANTAGONISTIC BIOACTIVE COMPOUNDS AGAINST UTI PATHOGENS - G. KALAIVANI,; N. HEMALATHA,; E. POONGOTHAI, (International Journal of Pharma and Bio Sciences, 2016)
The discovery, development and clinical use of antibiotics during the 20th century decreased substantially the morbidity and mortality from bacterial infections. Marine bacteria and fungi are of considerable importance as new promising sources for a huge number of biologically active products. For the present study multi antibiotic resistant pathogens from UTI patients were chosen. The brown alga Turbinaria conoides associated endophytic and epiphytic bacterial strains were isolated and screened for potential antagonistic activity against UTI pathogens using the Cross streak assay. Three potent antagonistic marine bacteria inhibiting growth of all tested pathogens were mass cultured for ethyl acetate extraction and concentration of extracellular bioactive products in broth medium. The S6-EP marine isolate inhibited the Gram positive and negative UTI pathogens of this study with minimum inhibitory concentration in the range of 250 µg – 500 µg/ml. The bioactive secondary metabolites of concentrated extract of marine strain S6-EP were characterized by Gas chromatography and Mass spectrometry (GC - MS).